Consideration for Dietary Nutrient Density and Energy Feeding Programs for Growing Large Male Broiler Chickens for Further Processing - Saleh, E.A.; Watkins, S.E.; Waldroup, A.L.; Waldroup, P.W. (International Journal of Poultry Science, 2003)
Three trials with identical experimental design were conducted to examine the effects of dietary nutrient density and energy feeding programs on male broiler chickens grown to heavy weights for further processing. Diets were formulated to provide a minimum of 107.5% of NRC (1994) amino acid requirements, maintained in proportion to dietary energy levels. Diets with different nutrient density were obtained by adding 0, 3, and 6% poultry oil (PO) while maintaining essential nutrients in a constant balance with energy. Diets within each age period (0 to 21 days, 21 to 42 days, and 42 to 63 days) had similar ratios of metabolizable energy to crude protein. Six feeding programs were obtained by either feeding these three levels of PO continuously to 63 d or by increasing the amount of PO in the diet at 21 d. Live performance was examined at 14, 21, 42, and 63 d and carcass composition was examined at 63 d. Dietary energy levels or feeding programs had no significant effect on body weight except at 42 d, which improved as PO was added to the diet. Feed intake was not significantly affected by feeding various levels of poultry oil or by utilizing different feeding programs. However, feed conversion at all ages showed a significant improvement as the level of supplemental PO increased. Calorie conversion was not affected at 14, 21, and 42 d. At 63 d, calorie conversion was significantly reduced when birds received diets with increased supplemental PO. Neither supplemental PO or feeding program affected the dressing percentage or yield of economically important carcass components at 63 d when examined on an absolute basis or as percentage of carcass weight. Abdominal fat content was not significantly influenced by level of supplemental poultry oil.